A Review of Cognitive Development: The Theory of Jean Piaget - Lather, Dr Ravinder (Innovative Research Thoughts, 2017)
Jean Piaget, a Swiss psychologist was particularly concerned with the way thinking develops in children from birth till they become young adults. To understand the nature of this development, Piaget carefully observed the behaviour of his own three kids. He used to present problems to them, observe responses slightly after the situations and again observe their responses. Piaget called this method of exploring development clinical interview. Piaget believed that humans also adapt to their physical and social environments in which they live. The process of adaptation begins since birth. Piaget saw this adaptation in terms of two basic processes: Assimilation and Accommodation. Assimilation. It refers to the process by which new objects and events are grasped or incorporated within the scope of existing schemes or structures. Accommodation. It is the process through which the existing schemes or structure is modified to meet the resistance to straightforward grasping or assimilation of a new object or event.